153 NEO-PTC-01 (BNT-221), an autologous neoantigen-specific T-cell product for adoptive cell therapy of metastatic melanoma. (9th November 2020) - Lenkala, Divya; Kohler, Jessica; McCarthy, Brian; Nelson, Michael; McGee, Jonathan; Kallin, Daniel; Sridar, Janani; Turcott, Paul; Harjanto, Dewi; Nijenhuis, Cynthia; Berg, Joost Van Den; Gaynor, Richard; et al.
Abstract : Background: Neoantigens are tumor-specific antigens that are important in the anti-tumor immune response. These antigens are not subject to central immune tolerance and are therefore potentially more immunogenic than tumor-associated antigens. NEO-STIM ®, our propriety ex vivo induction process, was developed to generate T-cell products specific to these neoantigens from the peripheral blood of patient. Here, we present the results of a proof of concept, pre-clinical study with multiple successful process engineering runs generating a neoantigen-specific T-cell product (NEO-PTC-01) using leukaphereses from metastatic melanoma patients. These products contain specific T-cell responses targeting multiple neoantigens from each individual patient's tumor. Methods: Patient-specific neoantigens were predicted using our RECON ® bioinformatics platform. Predicted high-quality neoantigens were utilized in our ex vivo stimulation protocol, NEO-STIM, in the process engineering runs of NEO-PTC-01. NEO-STIM is used to prime, activate and expand memory and de novo T-cell responses from both the CD4 + and the CD8 + compartment. High throughput flow cytometric analysis was performed to characterize the specificity and functionality (cytokine production and cytolytic capacity) of the induced T-cell responses. Results: Here we present the successful induction of 4–5 CD8 + and 4–7 CD4 + T-cell responses per patient, generated using peripheral blood mononuclear cells from multiple melanoma patients during these successful process engineering runs. We then extensively characterized these T-cell responses and demonstrate that these responses are functional, specific and have cytolytic capacity. Moreover, the induced T cells can recognize autologous tumor. Conclusions: NEO-STIM is a novel platform that generates ex vivo T-cell responses to high-quality neoantigen targets. NEO-PTC-01, the neoantigen-specific T cell product generated from this process, is a potent adoptive cell therapy targeting multiple immunogenic neoantigens in patients with metastatic melanoma.